If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + -2x = -1(x + 1) Reorder the terms: -5 + -2x = -1(1 + x) -5 + -2x = (1 * -1 + x * -1) -5 + -2x = (-1 + -1x) Solving -5 + -2x = -1 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -5 + -2x + x = -1 + -1x + x Combine like terms: -2x + x = -1x -5 + -1x = -1 + -1x + x Combine like terms: -1x + x = 0 -5 + -1x = -1 + 0 -5 + -1x = -1 Add '5' to each side of the equation. -5 + 5 + -1x = -1 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = -1 + 5 -1x = -1 + 5 Combine like terms: -1 + 5 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4
| 24/0.320 | | -3.2(2x-2.1)= | | 2z+5=3(z+4) | | -5.1+1.2= | | 6a-16=38 | | -9(-6+k)= | | (20+3x)/x | | x^2+y^2+x+y-1/2=0 | | 6x+7x-68=51-4x | | 25x^2-30x-26=0 | | (x+3)+(x+3)+(2x-6)+(2x-6)= | | (12*r)*13=0 | | 11s+7=8s-7 | | -8.1-1.8= | | 5q=7+2/3 | | -b-2b=6 | | V+5+4v=1+5v+3 | | 0.04m=-5.2 | | (3x+5)(7x-8)=0 | | -n+1=-n-6 | | (-7+w)6= | | (((n+5)*2)-8)/2 | | p+3/m-1 | | -8d-5d-7d=72 | | h(2)=16t^2+45t+1 | | -10a=160/7 | | 6x+8x-38=95-5x | | x^2+ix-2=0 | | 25+10[12-x]=5[2x-7] | | 8h+23=17 | | h(t)=16t^2+45t+1 | | -4.8-(-11.2)= |